ANALISIS FATIGUE PEGAS DAUN KENDARAAN TRUCK MITSUBISHI COLT DIESEL 110 PS PENGANGKUT SAYUR DENGAN METODE ELEMEN HINGGA - Muhamad, Farrastio Naufal; Fauzan, Shafwan; Maulana, Syahrul; ., Opan; Faisal, Moch; Fadillah, Rizki (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
Leaf springs are springs commonly used in vehicles and have a shape like a flat plate with a certain width and then subjected to lateral loads that make the plate bend. As a spring, the leaf spring has a function as a component of the suspension system to absorb shock or impact from the road surface and also withstand wheel vibrations so that these vibrations are not transmitted to the vehicle body. Failure of leaf springs on canter trucks is caused by uneven road conditions that give the maximum load on the rear leaf springs of the truck, causing the leaf springs to break due to repeated loading. In this research, it has the aim of obtaining the equivalent alternating stress, life cycle, fatigue sensitivity, and safety factor values from testing with a load of 10000 kg. This research process is to examine the specifications of 9-layer leaf springs.